Assessing the Quality of Student Thinking Directly: An Exploratory Study of Two Cohorts Entering Engineering Education in South Africa - Woollacott, Laurie; Snell, Dawn (South African Journal of Higher Education, 2016)
This paper presents the findings of an exploratory investigation involving the direct assessment of the quality of abstract thinking of two cohorts of South African university entrants who had very good school leaving qualifications. The investigation was prompted by the observation of difficulties these students seemed to have had in a first year engineering course with regard to conceptualization and problem solving that called for abstract thinking. The investigation was based on neo-Piagetian principles and the benchmarked findings indicated an alarming level of concrete thinking in tasks that called for abstract thinking. The paper argues that this is a manifestation of a problematic secondary education system and that quality of thinking has received inadequate research attention as a potentially significant factor influencing student retention and academic performance in the country. It argues further that such research should include a re-evaluation of current first year educational strategies with regard to the development of the quality of student thinking and that, to support this, additional research is needed to develop appropriate instruments for providing objective measures of the quality of student thinking. Based on the experience gained in the study, recommendations are made about directions such research could take.